Legal Proof of Capital Market Manipulation in Indonesia: Case 34/Pid.Sus-TPK/2020/PN.Jkt.Pst Analysis - Abilah, Rahma Christabel; Rasji, Rasji (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The legal framework contained in Articles 90 to 93 of the Law Number 8 of 1995 on Capital Market affirms the prohibition of market manipulation practices. Nevertheless, the effectiveness of law enforcement is often hindered due to the complexities involved in proving market manipulation, which include the perpetrators' sophisticated modus operandi, limitations of legal instruments, and weaknesses in investigative mechanisms. The PT Asuransi Jiwasraya case, as adjudicated in Judgment in the Criminal Corruption Case No. 34/Pid.Sus-TPK/2020/PN.Jkt.Pst dated October 12 th, 2020, illustrates the evidentiary complexities of market manipulation, given that such offenses were committed by white-collar criminals in a structured manner, employing nominees so that transactions appeared administratively legitimate. This research adopts a normative juridical method, using a statutory approach and case study analysis to examine regulatory weaknesses and propose an applicable evidentiary model. The findings reveal that the absence of specific evidentiary rules, the weakness of tracing mechanisms for market manipulation, and the limited capacity of law enforcement authorities constitute major obstacles in addressing such cases in Indonesia. The study proposes an ideal evidentiary model grounded in judicial decision analysis and the strengthening of the role of law enforcement authorities. These findings underscore the urgency of reforming capital market regulations to ensure more effective enforcement against market manipulation and to restore public confidence.